Pakistan : Report on the Observance of Standards and Codes-Data Module, Reassessment of Monetary Statistics; Response by the Authorities; and Detailed Assessment Using Quality Assessment Framework (DQAF). (IMF Staff Country Reports; Country Report ;, 2007)
This paper discusses key findings of the Report on the Observance of Standards and Codes on Data Module for Pakistan. Based on the review of Pakistan's statistical practices, recommendations are made that are aimed at strengthening Pakistan's adherence to the internationally accepted practices, as well as at enhancing the usefulness of its monetary statistics. For the central bank's survey, it is recommended to revalue the State Bank of Pakistan's Fund positions and gold assets on a monthly basis at end-month market exchange rates and market gold prices.